2001
DOI: 10.2214/ajr.176.2.1760507
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Knowledge of Chronologic Age on the Variability of Pediatric Bone Age Determined Using the Greulich and Pyle Standards

Abstract: Knowing chronologic age before assessing bone age radiographs does not affect the reproducibility of assessment. However, observers are more likely to interpret the radiograph as showing normal findings when chronologic age is known than if the interpretation is performed with the observer unaware of chronologic age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
29
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(39 citation statements)
references
References 25 publications
8
29
0
2
Order By: Relevance
“…Figure 3 supports this hypothesis. Such an effect was also reported by Berst et al [13], but our study displayed a more dramatic effect. This finding is a problem in a PACS-based environment, where in daily clinical routine it is virtually impossible to blind radiologists to the CA.…”
Section: Discussionsupporting
confidence: 91%
“…Figure 3 supports this hypothesis. Such an effect was also reported by Berst et al [13], but our study displayed a more dramatic effect. This finding is a problem in a PACS-based environment, where in daily clinical routine it is virtually impossible to blind radiologists to the CA.…”
Section: Discussionsupporting
confidence: 91%
“…These limitations and the difficulty of interpreting X-rays of an almost ossified hand raise doubts about the reliability of the method, when it is used to predict reaching legal adult age. Despite these limitations in accordance with previous studies [10,11,14,[23][24][25][26][27], our results showed that the GPM is a reproducible and repeatable method. This means that although it closely depends on the judgment of the person interpreting it, there is a high level of agreement between different readers in assessment of skeletal age.…”
Section: Discussionsupporting
confidence: 91%
“…The 4 residents wrote 482 reports according to the GP atlas (4 residents estimated 110, 112, 120 and 140 cases, respectively). The clinical information and chronological age were available to the 4 residents as part of their routine work [4]. To evaluate interobserver variance, we selected 50 radiographs for all 4 residents and the 2 attending radiologists to determine the BA in a blinded manner.…”
Section: Methodsmentioning
confidence: 99%
“…Although using the GP atlas is faster than the Tanner-Whitehouse method [2,3], BA estimation is still time-consuming as radiologists must carefully match left-hand films of children who are suspected to have abnormal maturation with standard plates from the GP atlases. Additionally, rater variability is the main shortcoming of this method that cannot be avoided [4]. As a solution to this problem, automated systems have been developed [5,6].…”
Section: Introductionmentioning
confidence: 99%